Energetic carbon precursors for micro-supercapacitor printing - Gellrich, Christin; Lochmann, Stefanie; Otto, Thomas; Grothe, Julia; Kaskel, Stefan (Materials Advances, 2021)
A highly energetic carbon precursor suitable for soft lithographic processing based on acetylene dicarboxylic acid is presented. High-resolution micro-supercapacitors with line width down to 500 nm are produced using solvent assisted nanoimprint lithography. The resulting nonporous carbons exhibit remarkably low specific resistance down to 6.9 × 10-5 Ω m pyrolyzed at 800 °C. The interdigital electrodes show excellent device capacitances of up to 1.32 mF cm-2 with an average capacitance retention of 97% after 10 000 cycles. Tailoring the performance is achieved by variation of electrode distances and carbonization temperatures. This journal is
CRIS-Team Scopus Importer:2022-04-14